EMPLOYEE PERFORMANCE DETERMINANTS, WITH GENDER AS A GROUP - Ni Luh Putu Sariani; Yenny Verawati; Gde Bagus Brahma Putra; Tjok Istri Sri Harwathy; Ida Bagus Swaputra (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
The purpose of this study is to analyze the influence of organizational commitment on employee performance; analyze the influence of organizational commitment on OCB; analyze the influence of OCB on employee performance; analyze the role of gender as the effect of moderation of organizational commitment on employee performance; analyze the role of gender as the effect of the moderating effect of organizational commitment on OCB, and analyze the role of gender as the effect of moderation on OCB on employee performance.. The population and sample were 45 respondents from the Notary Office in Bangli Regency with the saturated sampling method. The data collection technique was using a closed multiple-choice questionnaire and the partial least squares (PLS) data analysis approach was used. The results of the research show that the evaluation of the overall model seen from the coefficient of determination can already be said, Q-Square Predictive Relevance meets the requirements of existing and Goodness of Fit in a large position, the overall model is declared quite good. The conclusion of this study is that organizational commitment has a significant positive effect on employee performance has not been received. Organizational commitment has a significant positive effect on OCB received. OCB has a significant positive effect on employee performance is acceptable. Gender has not been tested as moderating of the effect of organizational commitment on employee performance, organizational commitment on OCB and OCB on employee performance.